The Investigation of Religious Character based on NU Traditions at Mts Miftahul Huda Silir Sari Labuhan Ratu - Tufani, Ahmad; Amirudin, Amirudin; Mispani, Mispani (International Journal on Advanced Science, Education, and Religion, 2025)
This program is implemented with an integrated approach in students' daily activities at school, both in academic and extracurricular activities. Character cultivation is carried out by providing real examples through the teacher's attitude, as well as strengthening the religious values taught by involving parents in supporting students' religious discipline at home. Evaluation of student character development is carried out continuously through behavior records and intense communication with parents. This research uses qualitative research methods with case study research (field research). By using data collection techniques in the form of observation, interviews and documentation. Test the validity of the data using triangulation. And the data analysis techniques are data reduction, data presentation, conclusions. The research results show that the NU-based religious character development program at MTs Miftahul Huda Silir Sari has had a positive impact on students' attitudes and behavior, especially in developing discipline, tolerance, honesty and concern for others. This program succeeded in creating a harmonious school atmosphere, based on moderate Islamic teaching values, and further strengthened the school's commitment to forming a young generation with noble morals in accordance with NU traditions. The contribution of this research theoretically enriches the study of character education based on local religious values. Practically, it provides a character development model that can be adopted by other educational institutions. Socio-culturally, this research shows the importance of preserving NU's traditional values in education. Meanwhile, in a policy context, these findings can be input into formulating contextual and effective character education programs.